Capitalist systems and income inequality - Marco Ranaldi; Branko Milanović (Luxembourg Income Study (LIS), 2020)
The paper investigates the relationship between capitalism systems and their levels of income and compositional inequality (how the composition of income between capital and labor varies along income distribution). Capitalism may be seen to range between Classical Capitalism, where the rich have only capital income, and the rest have only labor income, and Liberal Capitalism, where many people receive both capital and labor incomes. Using a new methodology and data from 47 countries over the past 25 years, we show that higher compositional inequality is associated with higher inter-personal inequality. Nordic countries are exceptional because they combine high compositional inequality with low inter-personal inequality. We speculate on the emergence of homoploutic societies where income composition may be the same for all, but Gini inequality nonetheless high, and introduce a new taxonomy of capitalist societies.
Keywords: D31; P51; 330; inequality; capitalism; Gini; compositional inequality